Delivering Innovative RDM Training: The immersiveInformatics Pilot Programme - Anna Shadbolt; Leo Konstantelos; Liz Lyon; Marieke Guy (International Journal of Digital Curation, 2014)
This paper presents the findings, lessons learned and next steps associated with the implementation of the immersiveInformatics pilot: a distinctive research data management (RDM) training programme designed in collaboration between UKOLN Informatics and the Library at the University of Melbourne, Australia. The pilot aimed to equip a broad range of academic and professional staff roles with RDM skills as a key element of capacity and capability building within a single institution.